PENGUASAAN KALIMAT EFEKTIF DAN PENGUASAAN DIKSI DENGAN KEMAMPUAN MENULIS EKSPOSISI PADA SISWA SMP - Fitriyani, Dwi (JURNAL PESONA, 2015)
AbstractWriting is a language skill used to communicate indirectly. Writing is a productive and expressive activity. Writing skill or composing is an ability to construct sentences properly and appropriately based on the language grammatical rules; good writing and effective depend on the sentence. This study examines the correlation between effective sentence mastery and diction mastery with exposition writing ability on SMP Negeri 1 Banyumas VII class the second semester. This study uses correlational method. Based on the result, the correlation between effective sentence mastery and diction mastery with exposition writing ability shows the determination coefficient in effective sentence mastery and diction mastery with exposition writing ability is 0,68 with effective sentence mastery and diction mastery toward exposition writing ability is 68%. The higher studentsâ effective sentence mastery the exposition writing ability is increasing. Otherwise, the diction mastery has close correlation with exposition writing ability. Â Key Words : Effective Sentence, Diction, Exposition Writing AbilityÂ